Electrical Stimulation to Promote Peripheral Nerve Regeneration. (June 2016) - Willand, Michael P.; Nguyen, May-Anh; Borschel, Gregory H.; Gordon, Tessa
Peripheral nerve injury afflicts individuals from all walks of life. Despite the peripheral nervous system's intrinsic ability to regenerate, many patients experience incomplete functional recovery. Surgical repair aims to expedite this recovery process in the most thorough manner possible. However, full recovery is still rarely seen especially when nerve injury is compounded with polytrauma where surgical repair is delayed. Pharmaceutical strategies supplementary to nerve microsurgery have been investigated but surgery remains the only viable option. Brief low-frequency electrical stimulation of the proximal nerve stump after primary repair has been widely investigated. This article aims to review the currently known biological basis for the regenerative effects of acute brief low-frequency electrical stimulation on axonal regeneration and outline the recent clinical applications of the electrical stimulation protocol to demonstrate the significant translational potential of this modality for repairing peripheral nerve injuries. The review concludes with a discussion of emerging new advancements in this exciting area of research. The current literature indicates the imminent clinical applicability of acute brief low-frequency electrical stimulation after surgical repair to effectively promote axonal regeneration as the stimulation has yielded promising evidence to maximize functional recovery in diverse types of peripheral nerve injuries.